Strategies for currency unification : the economics of currency competition and the case for a European parallel currency - Vaubel, Roland (Tübingen : Mohr, 1978)
This book is a study of strategies for currency unification, of their pre-conditions and implications, and of their advantages and disadvantages.
Bibliography: p. 419-471.
usc 2/8/17
Loans
Keywords: Monetary unions; Money; Europe--European Economic Community countries